Strengthening Brand Identity: Embracing Local Wisdom through Character Education Management - Istianatul Hasanah; Hefniy Hefniy; Abdul Wahid Zaini (Nurul Jadid University, 2023)
The focus of this study is to investigate the role and implementation of character education planning in Nurul Jadid Islamic Boarding School in maintaining the institution's brand identity and strong local values. This study discusses communication dynamics in the pesantren environment and the application of attribution theory in understanding community perceptions. This study explores how communication takes place in the context of pesantren and how attribution theory is used to understand how people interpret messages and actions from pesantren. The research method used is a case study that analyzes communication interactions in certain pesantren and interviews related community members. The results showed that communication in pesantren produces self-awareness, optimization of communication, building a positive image, public education, and collaboration. Attribution theory helps understand how society assigns meaning and interpretation to information received from pesantren. These findings provide valuable insight into the importance of effective communication in building a positive image and increasing public understanding of pesantren. This study's implication is to guide traditional Islamic educational institutions in strengthening brand identity and local values through a planned character education approach.